2020
DOI: 10.1371/journal.ppat.1008456
|View full text |Cite
|
Sign up to set email alerts
|

Fatal progression of experimental visceral leishmaniasis is associated with intestinal parasitism and secondary infection by commensal bacteria, and is delayed by antibiotic prophylaxis

Abstract: Leishmania donovani causes visceral leishmaniasis (VL), which is typically fatal without treatment. There is substantial variation between individuals in rates of disease progression, response to treatment and incidence of post-treatment sequelae, specifically post-kala-azar dermal leishmaniasis (PKDL). Nevertheless, the majority of infected people are asymptomatic carriers. Hamsters and mice are commonly used as models of fatal and non-fatal VL, respectively. Host and parasite genetics are likely to be import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
0
14
1
Order By: Relevance
“…Moreover, mice and humans differ in number of effector molecules such as defensin [5] , [6] and granulysin [7] and the capacity of human phagocytic cells to produce NO appears to be under much tighter regulation [8] , [9] . Furthermore, no infection of intestine is observed in mouse model [10] .…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, mice and humans differ in number of effector molecules such as defensin [5] , [6] and granulysin [7] and the capacity of human phagocytic cells to produce NO appears to be under much tighter regulation [8] , [9] . Furthermore, no infection of intestine is observed in mouse model [10] .…”
Section: Introductionmentioning
confidence: 94%
“…VL is characterized by presence of an enlarged liver and spleen, anemia, weight loss, and irregular fevers ( 2 ). Patients with VL often die within 2 years of contracting the disease if left untreated, commonly from subsequent infections or severe anemia ( 30 , 31 ). Although not seen in all VL species it is expected that darkening of the skin, particularly in India, is caused by the cytokine-induced production of adrenocorticotrophic hormone ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…The dysbiosis is marked by increased specific groups of bacteria that were related to the outcome of disease ( 38 ). Gut microbiota composition seems to be relevant in visceral leishmaniasis since it was recently shown that gut microbiota modulation by an antibiotic cocktail can improve the disease outcome in hamsters infected with L. donovani ( 39 ).…”
Section: Introductionmentioning
confidence: 99%